ENGLISH EDUCATION STUDENTS’ PERCEPTIONS OF TRANSLATOR PROFESSION IN THE ERA OF AI-ASSISTED TRANSLATION - Alam Muliawan, Sunanda; Fauzi, Iwan; Pratika, Dellis; Nasution, Hikmal Maulana; Jami, Sonia Vriska Yulinda (ENGLISH, 2026)
The rapid development of artificial intelligence and translation technologies has transformed the translation landscape and raised questions about the future relevance and sustainability of the translator profession. As AI-assisted translation tools become increasingly embedded in language practices, understanding how future language professionals perceive this profession becomes important. This study explores English Education students’ perceptions of the translator profession in the era of AI-assisted translation, focusing on familiarity, interest, perceived work prospects, and technological integration. Using a convergent parallel mixed-methods design, data were collected through questionnaires distributed to 30 English Education students selected through cluster sampling from a translation-related course at one of universities in Palangka Raya. Quantitative data from closed-ended items were summarized using descriptive statistics, while qualitative responses were analyzed thematically to identify recurring patterns in students’ perceptions. The findings indicate that most students are familiar with the translator profession mainly through academic exposure and translated media rather than direct professional experience. Students generally express positive but cautious interest, acknowledging the linguistic demands and professional responsibilities involved. Artificial intelligence is largely viewed as a supportive tool that improves efficiency but does not replace human judgment, cultural sensitivity, or contextual understanding. These findings contribute to translator education and AI-related translation studies by highlighting the importance of integrating technological awareness and professional orientation in preparing students for AI-assisted translation practices.